Teores de carboidratos em estacas lenhosas de mirtileiro - Oliveira, Rérinton Joabél Pires de (2010)
The aim at this work was to evaluate the alterations on carbohydrates metabolism of hardwood cuttings of blueberries cv. Delite, Powder Blue and Seleção 19. The starch and soluble sugars concentration were evaluated in blueberry branches at four different times in a first experiment (03/06, 04/07, 24/07 and 11/08/2008) and later the metabolism of carbohydrates were evaluated in harvested hardwood cuttings submitted to rooting conditions. It was verified that the cv. Powder Blue has higher starch concentration in the branches than Delite and Seleção 19. Hardwood cuttings of blueberry with low percentage of starch, when subjected to rooting, have resynthesis of starch. At the end of the winter, there is an increase in starch in the branches of woody blueberry. A higher amount of starch in the branches during the winter is associated to a higher rate of rooting.